2018
DOI: 10.1002/jcp.26328
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Effects of microRNA‐10a on synapse remodeling in hippocampal neurons and neuronal cell proliferation and apoptosis through the BDNF‐TrkB signaling pathway in a rat model of Alzheimer's disease

Abstract: The aim of this study was to research the effects of microRNA-10a (miR-10a) on synapse remodeling and neuronal cells in rats with Alzheimer's disease (AD) through BDNF-TrkB signaling pathway. Rat models of AD were established. The neuronal cells were allocated into blank, negative control (NC), miR-10a mimics, miR-10a inhibitors, K252a, and miR-10a inhibitors + K252a groups. Expressions of miR-10a, p38, PSD95, BDNF, cAMP-response element-binding protein (CREB), and tropomyosin receptor kinase B (TrκB) were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…The CREB is a key transcription factor, regulating synaptic and neural plasticity related genes [ 17 ]. According to We et al, the expression of BDNF is decreased in the AD rat model [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CREB is a key transcription factor, regulating synaptic and neural plasticity related genes [ 17 ]. According to We et al, the expression of BDNF is decreased in the AD rat model [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to AD and its link with miRNAs and BDNF, the expression level of miR-132 was increased via BDNF regulation [ 93 , 94 ]. Furthermore, miR-322, miR-30a-5p, miR-206, miR-195, miR-10a, and miR-163 were identified to target BDNF [ 16 , 61 , 96 98 ]. Interestingly, EA improved learning and memory in AD rats, promoted neurogenesis in AD, and maintained hippocampal LTP to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal overexpression of miR-30a-5p resulted in downregulation of BDNF protein [ 61 ]. Another dual-luciferase reporter gene assay demonstrated that miR-10a targeted BDNF, and the authors indicated that miR-10a restrains synapse remodelling and neuronal cell proliferation while promoting apoptosis in AD rats by inhibiting the BDNF-TrkB signalling pathway [ 98 ]. Furthermore, miR-322 is significantly increased with the decrease in BDNF in the AD mouse brain, and a luciferase reporter assay identified that miR-322 can directly conjugate to the 3′-UTR of BDNF [ 16 ].…”
Section: Main Textmentioning
confidence: 99%
“…Recently, the role of altered miRNAs in the diagnosis for AD has been extensively studied. Several miRNAs have been shown to regulate AD-relative genes, such as amyloid precursor protein (APP), beta-site APP cleaving enzyme 1 (BACE1), and brain-derived neurotrophic factor (BDNF) [21][22][23] . This ability of selected miRNAs to target mRNAs which are altered in disease conditions makes them potential candidate as therapeutics or as targets of therapeutics.…”
Section: Read Full Licensementioning
confidence: 99%